Labor Productivity during the Great Depression in UK Manufacturing - Robert A. Hart (Institute of Labor Economics (IZA), 2019)
This paper provides estimates of labor productivity for one-third of UK manufacturing during the Great Depression. It covers engineering and allied industries, and metal working industries. A unique data set of actual hours of work is combined with comparable real output and employment statistics. It establishes that output per worker-hour was countercyclical in the 1929-1932 peak-to-trough years of the Depression. This result has also been found for US manufacturing over the same period. Working time is found to play a crucial role the UK productivity response. Countercyclical productivity is discussed in terms of (i) the strong final output and consumer price deflations of 1929 to 1934, (ii) an absence of significant labor hoarding, and (c) diminishing returns to long weekly hours of work.
Keywords: O47; E32; N64; 330; labor productivity; Great Depression; diminishing returns to hours